Kemitraan dalam Pengembangan Komunikasi Publik Kelompok Informasi Masyarakat di Kota Malang - Pratama, Bayu Indra; Pratama, Muhammad Rizki; Praja, Bayu Amengku; Meirezaldi, Onni; Hisyam, Safarudin; Sekti Ari, Dessanti Putri; Putra, Irfan Kharisma; Alfattahu, Naufal Farras (Universitas Pahlawan Tuanku Tambusai, 2024)
The Community Service Team of the Faculty of Administrative Sciences, Universitas Brawijaya, has collaborated with the Malang Community Information Group Forum (Forum KIM) since 2020 to improve the public communication skills of the KIM members. Based on earlier observations, many KIM members still need help in public speaking and creating attractive organizational profiles. Therefore, the community service team organized a Public Speaking Organization Profile Workshop. This event was held on November 25, 2023, at the Rampal Celaket Village Hall, Malang, and involved KIM members from 31 villages. The workshop method uses on-spot practicals and discussion. The workshop successfully improved participants' understanding and practical skills in public communication, as evidenced by their enthusiasm and commitment during the training sessions. The results showed a significant increase in the confidence and communication skills of KIM members, which is expected to have a considerable positive impact on the effectiveness of public information delivery and their role as information gatekeepers in the community.